Phase Diagram of Li-Graphite Intercalation Compound Formed by the Charge/Discharge Reaction in Li-Ion Battery. Issue 7 (1st July 2022) - Fujimoto, Hiroyuki; Yamaki, Takahiro; Shimoda, Keiji; Fujinami, So; Nakatani, Tomotaka; Kano, Gentaro; Kawasaki, Mitsuo; Ogumi, Zenpachi; Abe, Takeshi
Abstract : The graphite negative electrode for Li-ion batteries was subjected to precision charge/discharge measurements at low current loads. The derivatives of the potential vs capacity curve and the potential vs C/Li composition curve were used to analyze elementary charge/discharge reactions. The number of peaks in the potential-capacity derivative curve increased with decreasing current load, and the elementary reactions, based on the formation of an unconfirmed superlattice structure, could be clearly separated and analyzed. By synchronizing these results with operando synchrotron X-ray diffraction data, a phase diagram of the Li-graphite intercalation compound formed by the charge/discharge reaction in Li-ion battery was established.